2020
DOI: 10.1029/2019gl085020
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Potential for Snow‐Ice Formation in the Arctic Ocean

Abstract: We examine the regional variations and long‐term changes of the potential for snow‐ice formation for level Arctic sea ice from 1980 to 2016. We use daily sea ice motion data and implement a 1‐D snow/ice thermodynamic model that follows the ice trajectories while forcing the simulations with Modern‐Era Retrospective analysis for Research and Applications, Version 2 and ERA‐Interim reanalyses. We find there is potential for snow‐ice formation in level ice over most of the Arctic Ocean; this is true since the 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 65 publications
4
23
0
Order By: Relevance
“…In this study, we use observations and model data to demonstrate the dual, insulating effect of snow on winter sea-ice growth. Building on previous work (Merkouriadi and others, 2017, 2020), we show that snow inhibits sea-ice growth. However, snow also reduces the effect of warm atmospheric temperatures during storms.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we use observations and model data to demonstrate the dual, insulating effect of snow on winter sea-ice growth. Building on previous work (Merkouriadi and others, 2017, 2020), we show that snow inhibits sea-ice growth. However, snow also reduces the effect of warm atmospheric temperatures during storms.…”
Section: Discussionsupporting
confidence: 76%
“…However, due to the thinning of Arctic sea ice and the projected increase in the total annual precipitation, the potential for snow‐to‐ice transformation will increase (Granskog et al, 2017; Vihma et al, 2014). Snow ice formation has a strong regional variability in the Arctic, and the largest potential is found in the ASA (Merkouriadi et al, 2020). Granskog et al (2017) found that the contribution of snow ice layers (without superimposed ice) to total ice thickness ranged from 6% to 28% with a mean of 20% in the north of Svalbard in 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The N‐ICE2015 in situ observations of snow and sea ice thickness, internal ice temperature, and atmospheric forcing document that north of Whalers Bay, there is only modest melting and also virtually no winter freezing despite negative air temperatures, due to insulation by the thick snow cover (e.g., Graham et al, 2019; Merkouriadi, Cheng, et al, 2017, 2020; Merkouriadi, Liston, et al, 2020). Strong melting only occurs when sea ice drifts south over near‐surface warm AW.…”
Section: Discussionmentioning
confidence: 99%
“…The sea ice cover in the Arctic Ocean is in transition to a new, thinner regime. This entails a decrease in the ratio of sea ice thickness to snow load, which increases the likelihood of sea ice flooding events (Granskog et al, 2017; Maslanik et al, 2007; Merkouriadi, Liston, et al, 2020; Stroeve et al, 2012). Ice thinning implies that the ice pack will be more fractured and mobile (Graham et al, 2019; P. Itkin et al, 2017; Spreen et al, 2011), which will increase atmosphere‐ocean interaction, in turn enhancing ocean mixing and, potentially, upper‐ocean vertical heat fluxes.…”
Section: Introductionmentioning
confidence: 99%